Estimating the human mutation rate from autozygous segments reveals population differences in human mutational processes - Vagheesh M. Narasimhan (Nature Portfolio, 2017)
Estimates of human mutation rates differ substantially based on the approach. Here, the authors present a multi-generational estimate from the autozygous segment in a non-European population that gives insight into the contribution of post-zygotic mutations and population-specific mutational processes.